Textile materials as barriers against electromagnetic radiation - Šaravanja, Bosiljka; Malarić, Krešimir; Pušić, Tanja (2019)
The accelerated development of textile products that have shielding properties against electromagnetic (EM) radiation excites the interest of scientists, the textile and clothing industry in the manufacture of woven fabrics, knitted fabrics and clothing with shielding properties. This paper deals with the investigation of the shielding effect of the electroconductive fabric to be used for manufacturing protective clothing consisting of textile and non-textile components. The textile component is a cotton-modacrylic blend, and the non-textile component is an inox yarn inserted into the fabric every 1 cm in the transverse direction of the fabric. The fabric was finished using solvents in the processes of dry and wet cleaning as potential care processes. The measurement results of shielding fabric properties have shown that the degree of shielding is better preserved after 10 cycles of wet cleaning than after dry cleaning.
Bibliografija: 23 jed.
Abstract.
Keywords: Elektroprevodna tkanina -- Elektromagnetsko zračenje -- Zaštitno djelovanje